Design, synthesis, structural characterization by IR, 1H, 13C, 15N, 2D-NMR, X-ray diffraction and evaluation of a new class of phenylaminoacetic acid benzylidene hydrazines as pfENR inhibitors - Samal, Ramanuj P.; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Bwalya, Angela Gono; Tasdemir, Deniz; Joshi, Ramesh A.; Rajamohanan, P. R.; Puranik, Vedavati G.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2013)
Recent studies have revealed that plasmodial enoyl-ACP reductase (pfENR, FabI), one of the crucial enzymes in the plasmodial type II fatty acid synthesis II (FAS II) pathway, is a promising target for liver stage malaria infections. Hence, pfENR inhibitors have the potential to be used as causal malarial prophylactic agents. In this study, we report the design, synthesis, structural characterization and evaluation of a new class of pfENR inhibitors. The search for inhibitors began with a virtual screen of the iResearch database by molecular docking. Hits obtained from the virtual screen were ranked according to their Glide score. One hit was selected as a lead and modified to improve its binding to pfENR; from this, a series of phenylamino acetic acid benzylidene hydrazides were designed and synthesized. These molecules were thoroughly characterized by IR, 1H, 13C, 15N, 2D-NMR (COSY, NOESY, 1H-13C, 1H-15N HSQC and HMBC), and X-ray diffraction. NMR studies revealed the existence of conformational/configurational isomers around the amide and imine functionalities. The major species in DMSO solution is the E, E form, which is in dynamic equilibrium with the Z, E isomer. In the solid state, the molecule has a completely extended conformation and forms helical structures that are stabilized by strong hydrogen bond interactions, forming a helical structure stabilized by N-H...O interactions, a feature unique to this class of compounds. Furthermore, detailed investigation of the NMR spectra indicated the presence of a minor impurity in most compounds. The structure of this impurity was deduced as an imidazoline-4-one derivative based on 1H-13C and 1H-15H HMBC spectra and was confirmed from the NOESY spectra. The molecules were screened for in vitro activity against recombinant pfENR enzyme by a spectrophotometric assay. Four molecules, viz. 17, 7, 10, and 12 were found to be active at 7, 8, 10, and 12m concentration, respectively, showing promising pfENR inhibitory potential. A classification model was derived based on a binary QSAR approach termed recursive partitioning (RP) to highlight structural characteristics that could be tuned to improve activity.
Keywords: ADMET; docking; enoyl-ACP reductase; FabI; hydrogen bonding; NMR; phenylaminoacetic acid benzylidene hydrazine; Plasmodium falciparum; Plasmodium falciparum enoyl-ACP reductase; QSAR; recursive partitioning; X-ray diffraction

Discontinuous two step flow synthesis of m-aminoacetophenone - Tibhe, Jagdish; Sharma, Yachita; Joshi, Ramesh A.; Joshi, Rohini R.; Kulkarni, Amol A. (Green Processing and Synthesis, 2014)
The continuous flow nitration of acetophenone followed by reduction of the meta isomer has been demonstrated using simple tubular reactors. Because of ease of separation of the desired isomer from the first step, both steps are made continuous, but separately. The continuous flow nitration was carried out in a safe manner in a shorter reaction time than the conventional approach. The choice of micromixer was seen to affect the performance of the nitration reaction. The effect of different parameters on the yield of the desired product was studied. The reduction step with sodium sulfide was found to be economical and could be carried out efficiently at 70 degrees C using sodium sulfide in ethanol, using a silicone tube. Both steps were demonstrated for several hours, yielding a sufficiently large quantity (similar to 100 g) of m-aminoacetophenone at lab scale in a single day using simple tubular reactors.
Keywords: acetophenone; continuous flow synthesis; microreactor; nitration; reduction

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis